Research on localized marketing strategies in China of Yum! Brands, Inc. - Lin, Yangyang; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
Yum! Brands, Inc. has always been committed to capturing the Chinese market and has successfully adopted brand marketing strategies. With the rapid development of the Chinese market economy, Yum! Brands, Inc. has gained tremendous opportunities in one of the most important markets in the world. However, the fierce competition in the context of consumer upgrading also brings challenges. In the current market environment, consumers demand more in terms of products, dining environment, services, and experiences, while demonstrating personalized and diversified needs. As a result, Yum! Brands, Inc. is faced with the essential task of adapting to market development and meeting the changing needs of consumers to maintain a competitive advantage. This study investigates the marketing strategy of Yum! Brands, Inc. in the Chinese market by using PEST and SWOT analyses through the literature research method. The study aims to promote Yum! Restaurant Group’s market influence and stable development, as well as to provide a reference for similar foreign restaurant companies’ local marketing strategies in China.